The demand for urban transport: An application of discrete choice model for Cadiz - Candelaria Barrios Gonzalez; Maria Angeles Martinez Navarro (European Regional Science Association (ERSA), 1998)
The study of the demand for transport has among others applications, the valuation of travel time saving that is a very important question in cost-benefit analysis, and to adopt transport policy tools. Since McFadden developed a discrete choice model for travel demand, it has usually been the application of this model to study the individual behaviour when he has to choice among transport modes. Citizens of big cities have to face traffic congestion; pollution, wasted time in travels and fuel, noise, stress and accidents are the costs imposed by congestion to society, elements that reduce the quality of life in cities. Public transport is a real alternative to private transport that is socially less expensive, for this reason this paper tries to forecast travel demand for public transport in Cadiz when travelling have to choice between public or private transport, using a discrete choice model. The results of this analysis (travel demand, value of time, elasticities) can be used to design transport policies that could reduce congestion.
Keywords: 330